PERAN ASSOCIATION INTERNATIONALE DES ÉTUDIANTS EN ECIENCES ÉCONOMIQUES ET COMMERCIALES (AIESEC) DALAM MENDORONGSUSTAINABLE DEVELOPMENT GOALS (PENDIDIKAN BERKUALITAS) DI INDONESIA (2016 - 2019) - Deandra Diffa Aisyah, (2021)
The occurrence of globalization makes it easier for Non-Governmental Organizations (NGOs) to provide services to public, without profiting their activities. One of the NGO called AIESEC, in which has an ongoing partnership with the United Nations for the Sustainable Development Goals (SDGs). With that, AIESEC has a role and seperated into branches in Indonesia to carry out programs that are formed based on the SDGs goals, especially the number 4, about quality of education goals (2016-2019). This study aims to determine the role played by AIESEC in Indonesia in promoting the SDGs (Quality Education) program in Indonesia (2016-2019). This study uses an approach with research methods including data collection and data analysis. Data collected through interviews as primary data and literature as well as various other sources for secondary data. This research framework uses role theory and the concept of Non Governmental Organizations. The results of this study explain that AIESEC in Indonesia organizes the Global Volunteer program (2016-2019) by distributing volunteers spread through AIESEC local committees in such as in West Sumatra, South Sulawesi, and West Java to encourage contributions to the SDGs of quality education.